Evaluating the effectiveness of the blended learning station rotation model: A meta-analysis of student learning outcomes - Ramadan, Syahri; Istiyono, Edi; Farisiyah, Umi; Setyaningsih, Kris; Mustakim, Siti Salina Binti (Program Pascasarjana Universitas Negeri Yogyakarta, 2025)
This paper is analyzing the effect of the blended learning station rotation model on students' learning outcomes through a meta-analytic approach. The background of this research stems from the increasing use of digital technology in education, particularly after the COVID-19 pandemic, which encouraged teachers to integrate face-to-face and online learning into a unified instructional strategy. The station rotation model is considered adequate as it offers flexibility in learning time, facilitates differentiated learning, and enhances interaction between teachers and students. However, previous studies have shown varying levels of effectiveness, necessitating a comprehensive synthesis to gain an overall understanding of its impact on learning outcomes. This study employs the meta-analysis method following the PRISMA, which include the stages of identification, screening, eligibility, and inclusion. Sources obtained from indexed international journal articles, with inclusion. The results revealed that the station rotation model had a positive and significant effect on students' learning outcomes, with a moderate to high category of influence. Furthermore, moderators such as educational level, subject matter, duration of intervention, and research location were found to affect the magnitude of its impact. This study reaffirms that implementing the station rotation model can be an effective learning strategy to improve learning outcomes, particularly when integrated with adaptive instructional design and relevant digital media. There are expected to serve as a reference for educators, curriculum developers, and policymakers in optimizing the application of the blended learning model, specifically the station rotation type, at various educational levels. Future researchers are encouraged to expand the scope of inquiry to include non-cognitive variables such as motivation, learning engagement, and 21st-century skills, thereby providing a more comprehensive picture of the model's effectiveness.